Meta-analysis of randomized controlled trials on the efficacy and safety of ondansetron in preventing postanesthesia shivering. (November 2016) - Li, Min; Hu, Xiaolan; Tan, Yuan; Yang, Baoping; Li, Kun; Tang, Zhenyu
Abstract: Objectives: Considerable controversy exists regarding the efficacy of ondansetron in preventing postanesthesia shivering (PAS). We performed a meta-analysis of randomized controlled trials to examine the controversy. Materials and Methods: Randomized controlled trials assessing the effect of ondansetron on the prevention of PAS were identified from electronic databases (PubMed and EMBASE). The meta-analysis was performed with the fixed-effect model or random-effect model according to heterogeneity. Results: Twelve trials randomized clinical trials met the inclusion criteria including 1205 subjects. Compared with placebo (saline), ondansetron was associated with a significant reduction of PAS (relative risk 0.33; 95% confidence interval, 0.21–0.51), Substantial heterogeneity was observed between trials ( P  = 0.0002; I 2  = 71%). Trial sequential analysis showed that the cumulative Z-curve crossed the trial sequential monitoring boundary for benefit establishing sufficient and conclusive evidence. Meta-analysis with all five studies using a fixed-effects model suggested that ondansetron and meperidine have similar effects on the prevention of PAS (relative risk, 0.86; 95% confidence interval, 0.66–1.11), the heterogeneity was not significant ( P  = 0.34; I 2  = 11%). No significant association of ondansetron with bradycardia was found both comparison with placebo and meperidine. Conclusions: Treat with ondansetron is safe, and may reduce PAS. This finding encourages the use of ondansetron to prevent PAS, but, more high quality randomized clinical trials are still warranted to confirm the effects of different doses of ondansetron on PAS. Highlights: Compared with placebo, ondansetron was associated with a significant reduction of PAS. Meta-analysis with all five studies suggested that ondansetron and meperidine have similar effects on the prevention of PAS. More high quality RCTs are still warranted to confirm the effects of different doses of ondansetron on PAS.